The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.7554/elife.02482
|View full text |Cite
|
Sign up to set email alerts
|

SETD2 is required for DNA double-strand break repair and activation of the p53-mediated checkpoint

Abstract: Histone modifications establish the chromatin states that coordinate the DNA damage response. In this study, we show that SETD2, the enzyme that trimethylates histone H3 lysine 36 (H3K36me3), is required for ATM activation upon DNA double-strand breaks (DSBs). Moreover, we find that SETD2 is necessary for homologous recombination repair of DSBs by promoting the formation of RAD51 presynaptic filaments. In agreement, SETD2-mutant clear cell renal cell carcinoma (ccRCC) cells displayed impaired DNA damage signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
180
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(191 citation statements)
references
References 52 publications
9
180
0
2
Order By: Relevance
“…SETD2 protein is responsible for H3K36me3, which may lead to chromatin accessibility changes (23,24) and hinder mismatch repair (MMR) (25), and eventually cause RNA processing defects and promote oncogenesis (26). Previous studies support SETD2's role as a tumor suppressor in ccRCC (27). In our present study, low SETD2 expression was found to be associated with an aggressive phenotype of ccRCC, and was identified as an independent prognostic factor in two independent ccRCC cohorts.…”
Section: Discussionsupporting
confidence: 61%
“…SETD2 protein is responsible for H3K36me3, which may lead to chromatin accessibility changes (23,24) and hinder mismatch repair (MMR) (25), and eventually cause RNA processing defects and promote oncogenesis (26). Previous studies support SETD2's role as a tumor suppressor in ccRCC (27). In our present study, low SETD2 expression was found to be associated with an aggressive phenotype of ccRCC, and was identified as an independent prognostic factor in two independent ccRCC cohorts.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, SETD2 depletion seemed to favor repair by MMEJ. 24 Importantly, neither SETD2 recruitment nor increased H3K36me3 levels were found at DSBs, [22][23][24][25] suggesting that pre-established H3K36me3 channels active genes to HR repair. Notably, we found that RAD51 recruitment at HR-prone DSBs also depends on the lens epithelium-derived growth factor (LEDGF)/p75, which possesses a PWWP domain for H3K36me3-recognition.…”
Section: Function Of H3k36me3 In Dsb Repair Pathway Choicementioning
confidence: 99%
“…Indeed, we showed that depletion of the main H3K36me3 histone methyltransferase, SETD2, 18 is necessary for HR repair of "HR-prone" DSBs. 22 Concomitantly, 2 other groups reported the critical function of human SETD2 in homologous recombination 23,24 using other experimental systems such as I-SceIand radiation-induced DSBs. Furthermore, SETD2 depletion seemed to favor repair by MMEJ.…”
Section: Function Of H3k36me3 In Dsb Repair Pathway Choicementioning
confidence: 99%
“…This histone methylation is associated with open heterochromatin and reduced CpG methylation 159,158 , and changes in heterochromatin structure (such as nucleosome rearrangement) can alter the accessibility of the spliceosome machinery to genes and alter the expression of splice-variants. SETD2 mutations could, therefore, change the expression levels and functional structure of many genes 160 . H3K36Me3 is required for serine-protein kinase ATM and TP53-mediated DNA damage checkpoint activation 161 and the recruitment of the DNA mismatch repair protein Msh2 (also called hMutSα) 162 , suggesting that loss of SETD2 function combined with PBRM1 mutations could increase genomic instability and prevent correct cell-cycle checkpoint control.…”
Section: Histone Modification In Rccmentioning
confidence: 99%